Towards a Satisfactory Future—Multiprofessional Rehabilitation for Young Persons with ADHD or ASD - Hennariikka Heinijoki; Maarit Karhula; Pirjo Vuoskoski; Matti Munukka; Riku Nikander; Riitta Seppanen-Jarvela (Disabilities)
There is a lack of knowledge about what kind of support should be offered in adulthood for persons with attention-deficit/hyperactivity disorder (ADHD) or autism spectrum disorder (ASD) to promote inclusive participation in meaningful life domains. The core components of multiprofessional rehabilitation intervention for young adults are explored from the perspective of multiprofessional teams. This qualitative study adopts a pragmatic perspective on the core components of rehabilitation. Twenty-six professionals participated in vignette-based focus group interviews (n = 5), and thematic reflexive analysis was used to abductively analyze the data. A total of ten core components were identified. Nine of them were aggregated into three categories: (1) rehabilitation readiness (two core components), (2) adaptive progress in personal goals (four core components), and (3) rehabilitation continuum (three core components). The overarching tenth core component is focusing on the personal goals of daily life, work, studies, and social interaction. A collaborative relationship between the client and professional is essential to ensure adaptive progress and to foster clients’ self-determination. The focus should be on strengths and solutions instead of deficits and challenges. To establish rehabilitation continuum, it is essential to collaborate within the clients’ networks and to promote awareness and inclusive opportunities for working and studying for people with ADHD and ASD.